Mineral chemistry (biotite, muscovite, garnet, and plagioclase) in the Kathmandu and Gosainkund regions, central Nepal Himalaya - Rai, S. M.; Guillot, S.; Upreti, B. N.; Pecher, A.; Fort, P. Le (Journal of Nepal Geological Society, 2004)
The greenschist- to granulite-facies rocks in the Kathmandu and Gosainkund regions are divided into three tectonic units on the basis of structure, lithology, and metamorphism. The Gosainkund Crystalline Nappe (GCN) corresponds to the southward extension of the Higher Himalayan Crystallines (HHC), which thrusts over the Kathmandu Crystalline Nappe (KCN) along the Main Central Thrust (MCT). The GCN and KCN thrust over the Lesser Himalaya (LH) along the MCT and the Mahabharat Thrust (MT), respectively. Systematic traverses with the microprobe of four minerals (i.e. biotite, muscovite, garnet, and plagioclase) from all the three units were carried out to study their chemical variations. Most of the biotite compositions from all units belong to the annite compositional field. There is an inverse relationship between the Ti and the Mg number (Mg2+/ (Mg2++Fe2+) and the latter increases from the top to bottom section of the KCN. The LH biotites resemble the bottom composition of the KCN whereas the GCN biotite compositions are quite scattered. However, the Ti-Mg number trend does not seem to be related directly to the grade of metamorphism. The muscovites from the KCN are rich in FeO while the muscovites from other two units are rich in Al2O3. In the KCN, the almandine and pyrope contents in garnet decrease from bottom to top section, while the grossular and spessartine contents in garnet increase. This trend is consistent with the prograde metamorphic evolution observed in the field. The composition of garnets from the bottom to the top section of the GCN does not show any systematic variation, but in the upper section, where sillimanite appears, the almandine con tent decreases and the spessartine content slightly increases. This variation in composition suggests a polyphase metamorphic evolution. The albite content of plagioclase decreases from the lower to upper section in the KCN while there is not any systematic variation in the GCN. The P-T conditions record the good preservation of inverse metamorphism in the LH below the MCT. The comparison of P-T results between the KCN and the GCN suggests that exhumation of the KCN was followed by the exhumation of the GCN.